Conducting Design Reviews in a Digital Engineering Environment. Issue 4 (9th February 2023) - Blackburn, Mark R.; Kruse, Benjamin
ABSTRACT: This paper discusses how digital signoffs can enable new operational paradigms for business operations, digital engineering reviews, and contracts. The paper explains what digital signoffs are in the context of their use with model‐based systems engineering methods, which is how this concept and construct has evolved. The paper discusses how they are created in the current toolset. This paper explains the benefits of why digital signoffs are valuable, in addition to where they can be placed within models, and when they might be used. Finally, we discuss how digital signoffs might evolve as add‐on capabilities for digital engineering more broadly.